2022
DOI: 10.1007/s10389-022-01708-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, mental and physical health during the Covid-19 outbreak: longitudinal predictors of suicide ideation in Germany

Abstract: Aim Suicide ideation has increased since the outbreak of Covid-19 in many countries. The present longitudinal study investigated potential predictors of suicide ideation. Subject and methods Data of 406 participants from Germany (age M = 27.69, SD = 6.88) were assessed via online surveys in spring 2020 (baseline, BL) and in spring 2021 (follow-up, FU). Results The current results reveal a significant increase in sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 84 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…The presence of an effective coping mechanism such as sport, religion or a hobby might reduce the suicidal ideation through distracting from repetitive thoughts, releasing stress, or believing in a higher purpose. The protective effect of such a coping mechanism can be found in the literature, since having little time for hobbies and giving low importance to religion has been previously associated with higher risk of suicidal ideation (Lamlé et al, 2023), while regular physical activity has been found to prevent stress and suicidal ideation (Brailovskaia et al, 2023; Koo & Kim, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an effective coping mechanism such as sport, religion or a hobby might reduce the suicidal ideation through distracting from repetitive thoughts, releasing stress, or believing in a higher purpose. The protective effect of such a coping mechanism can be found in the literature, since having little time for hobbies and giving low importance to religion has been previously associated with higher risk of suicidal ideation (Lamlé et al, 2023), while regular physical activity has been found to prevent stress and suicidal ideation (Brailovskaia et al, 2023; Koo & Kim, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Brailovskaia et al found a significant increase in suicidal ideation and suicide rates among the public during the COVID-19 pandemic ( 89 ). The American clinical psychologist Beck ( 90 ) proposed a cognitive model of depression that argues that the underlying cognitive schema and cognitive theoretical assumptions of depressed individuals are at the root of patients' negative attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be interpreted as follows: PMH is an important protective factor that can buffer potential negative effects of the pandemic such as addictive SMU [ 28 ]. Yet, a comparison of the PMH level between 2020 and 2021 revealed a significant decrease due to the burdensome experiences since the pandemic outbreak [ 30 ]. The decrease in PMH could increase the risk for addictive SMU.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we could hypothesize that PMH might also reduce the risk of addictive SMU that results from COVID-19 burden. However, recent research described a decrease of PMH since the pandemic outbreak [ 30 ]. Therefore, it seems reasonable to consider an additional protective factor against addictive SMU.…”
Section: Introductionmentioning
confidence: 99%